Effects of corn oil ingestion on the intestinal mucosa of normal dogs - An, Su-Jin; Kim, Young Joo; Hong, Il-Hwa; Jung, Dong-In (Frontiers in Veterinary Science, 2024)
IntroductionWe assessed corn oil’s oral effectiveness in detecting small bowel changes in healthy dogs through ultrasonography, endoscopy, and histopathology. We hypothesize that corn oil ingestion will not significantly increase the visibility of lymphatics and lacteals in healthy dogs.MethodsFive healthy male beagles were studied under institutional guidelines. The small intestine’s mucosal changes were observed post corn oil consumption (0.5 mL/kg) at various time intervals using ultrasonography, endoscopy, and histopathology. Ultrasonography was employed in real-time, and mucosal echogenicity scores were assigned at multiple time points. Endoscopic and capsule endoscopic examinations were conducted weekly at different intervals post oil consumption, with biopsy samples taken from the duodenal and ileal mucosa for histopathological evaluations.ResultsUltrasonographic evaluations showed no pathological conditions in any dog. While conventional endoscopic evaluations reflected normal variation, capsule endoscopy revealed significant duodenal and jejunal mucosal changes 3 h post-ingestion, but not in the ileum. Histopathological evaluation indicated a transient rise in the dilation of ileum villi 3 h post-ingestion, reducing by 12 h.ConclusionIn conclusion, this study demonstrated that the observed physiological changes in the small intestinal mucosa, including lymphatic dilation, hyperechoic speckles, and stripes, were within the normal range after oil ingestion in healthy Beagle dogs.